HUBUNGAN DUKUNGAN BIDAN DENGAN PEMERIKSAAN PMTCT (PREVENTION MOTHER TO CHILD TRANSMISSION) PADA IBU HAMIL DI PUSKESMAS KASIHAN II BANTUL - Esitra Herfanda; Indah Pratiwi (JURNAL KEBIDANAN KESTRA (JKK), 2020)
HIV and AIDS transmission to infants can be prevented by comprehensive and effective PMTCT (Prevention Mother to Child Transmission) efforts in health care facilities. The role of the midwife in encouraging pregnant women to conduct PMTCT examinations is to provide support in the form of information, appreciation, instrumental and emotional information about HIV and AIDS thoroughly to the client until the client understands and gives the permission to conduct PMTCT examinations. The purpose of this study was to determine the correlation between midwife’s support and PMTCT examinations of pregnant women at Kasihan II Primary Health Center of Bantul. This research was conducted using observational analytic methods with cross sectional approach. Data collection techniques employed accidental sampling as many as 40 pregnant women as the respondents. The research instrument was a questionnaire with chi square as data analysis. The results of the study obtained showed that 80% among 40 respondents received good support, and 82.5% conducted PMTCT examinations. There was a correlation between midwife’s support and PMTCT examinations for pregnant women in Kasihan II Primary Health Center of Bantul with p value = 0.000 (p <0.05). Thus, it can be concluded that there was a correlation between midwife’s support and PMTCT examination for pregnant women at Kasihan II Primary Health Center of Bantul. Keywords: Midwife, Support, PMTCT.